Neonatal necrotizing enterocolitis rat model attenuated by a remote ischemic preconditioning in the pregnant - Gomes,Rúdnei de Oliveira Luciano (2017)
Abstract Purpose: To evaluate the effect of remote ischemic preconditioning (r-IPC) administered to pregnant rats, in the ileum of newborn rats subjected to hypoxia and reoxygenation. Methods: We used three pregnant rats and their newborn rats distributed in three groups: 1) Control (C) - Newborn rats born from a pregnant rat which did not undergo any intervention; 2) Hypoxia-Reoxygenation (H/R) - Newborn rats born from a pregnant rat which did not undergo any intervention, and were subjected to hypoxia-reoxygenation; 3) Remote Ischemic Preconditioning (r-IPC) - newborn rats born from a pregnant rat which was subjected to remote ischemic preconditioning twenty-four hours before giving birth and the newborn rats were subjected to hypoxia-reoxygenation. Segments of ileum were prepared for histological analysis by HE and immunohistochemistry by the Ki67 to evaluate cell proliferation, crypt depth and villus height and evaluation of apoptosis by cleaved caspase-3. Results: The intensity of the lesions was lower in the r-IPC than in the H/R group, showing significant difference (p<0.01). The r-IPC group showed a higher proliferative activity compared to the H/R group (p<0.01), with deeper crypts (r-IPC > H/R - p < 0.05), and higher villi, showing significant difference (r-IPC > H/R - (p <0.01). The occurrence of apoptosis in the H/R group was lower in comparison to groups C and r-IPC, with significant difference (H/R < r-IPC; p<0.05). Conclusion: The remote ischemic preconditioning applied to the pregnant rat protected the ileum of newborn rats subjected to hypoxia and reoxygenation, with decreased intensity of the lesions in the ileum mucosa and preservation of proliferative activity, keeping the villus height and crypt depth similar to group C.